Analysis of Land and Sea Temperatures Trend During 1985-2021 Period to Understand Local or Global Warming Effect in Bengkulu City - Arya J Akbar; Ashar Muda Lubis (Indonesian Review of Physics, 2022)
Global warming is a phenomenon where the earth's temperature rises drastically. The temperature increase causes negative impacts on the environment globally. Bengkulu City, Indonesia, is situated with a growing population and land-use change that may cause temperature rise. This research aimed to analyze the temperature change in the land and sea area of Bengkulu City. To understand the local or global factors influencing temperature changes in Bengkulu City, we also studied the correlation between land and sea temperatures. The temperature data were obtained from BMKG and NOAA PSL. Firstly, we analyzed the temperature trendlines for the last 36 years. Then we evaluated the coefficient determination (R2) value to determine the correlation between sea and land temperatures. The results show that during the last 36 years, the sea temperature is increased by 0.40 °C, while the land temperature is increased by 1.07 °C. Moreover, we found a relatively weak correlation between sea and land temperature, with a 10.7% correlation. We argued that the increased temperature in Bengkulu City land is associated with land change use and rising population in the last few decades, which means the local factor affected the land temperature changes. On the other hand, global phenomena (IOD and ENSO) influenced sea temperature changes, which means the global factor affected the sea temperature changes. The rising land temperature is relatively high; hence it is necessary to understand better what parameters are causing temperature changes that may affect the physical environment in Bengkulu, Indonesia.